Effectiveness of reinforcement program on adherence toward short peripheral catheter (SPC) care guidelines among registered nurses working in pediatric wards of a tertiary care hospital - S Shivani; Hepsi Bai Joseph (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Short peripheral catheterization is the common procedure performed in every hospital with patients' admittance. It becomes challenging when it comes to children and requires more knowledge and skills. The aim of the current study was to assess the effectiveness of the reinforcement program on adherence to short peripheral catheter (SPC) care guidelines among registered nurses. MATERIALS AND METHODS: A quasi-experimental study was conducted among 44 registered nurses by observing 96 SPC care events before and after the reinforcement program in pediatric wards of a tertiary care hospital in Eastern India. The study was conducted in a tertiary care public hospital in Eastern India in 2019, and the data collection tool included children's and nurses' socio-demographic data and an observation checklist on intravenous catheterization care. Descriptive statistics were used to explain the participant characteristics, and McNemar's test was used to identify the adherence to SPC care guidelines. RESULTS: There was a statistically significant improvement in most steps, such as hand washing, gloving, tray preparation, documentation initiation, maintenance, and removal (P = 0.001). A statistically significant reduction in the early stage of phlebitis was found from 66.7% in pre-intervention to 37.5% in post-intervention (P = 0.027). CONCLUSIONS: The majority of nurses adhered to SPC care guidelines after the reinforcement program. From the study findings, it is recommended that regular reinforcement related to peripheral catheter care acts as a stimulant to adhere to SPC care guidelines. The nursing administration should take initiative by conducting in-service training for the nurses, which motivates them toward practicing quality nursing care.